Researching health behaviour in 'real time': Methodological insights from a prospective study on Olympic hopefuls. Issue 1 (April 2019) - Schubring, Astrid; Barker-Ruchti, Natalie; Post, Anna; Pettersson, Stefan
In this article, we share our experience of navigating qualitative longitudinal research with a 'hard to recruit' population. To detail design conception, methodological challenges and insights, we draw on the case of a 1-year-long study on health behaviour in Olympic hopefuls. In order to accompany 12 athletes who aimed to qualify for either an Olympic Games (n = 10) or a World Championship (n = 2), we developed and implemented a career background questionnaire; semi-structured interviews; weekly web surveys; a training observation and a compilation of competition results. Based on the longitudinal research experience, we present project management and project data of the Paths-to-Rio study to discuss the challenges we faced, including gaining access to an elite population, their retention and anonymity. We further outline insights the prospective study gave us on the value of missing data as data and on the benefits participants described in terms of learning through research involvement. We conclude with recommendations for future qualitative longitudinal research.